Kepemilikan Tanah Sebagai Palaku Dalam Perkawinan Adat Dayak Ngaju Terhadap Status Hukum Dan Implikasinya Dalam Sengketa Perceraian (Studi Kasus Putusan Pengadilan Tinggi Palangka Raya Nomor 63/PDT/2020/PT. PLK) - Rahmah; Pelu, Ibnu Elmi AS; Helim, Abdul (Kartika: Jurnal Studi Keislaman, 2025)
This study explores the Dayak Ngaju customary marriage in Central Kalimantan incorporates unique elements of indigenous legal values, one of which is the practice of palaku or dowry, which may take the form of land. This study examines the legal status of land used as palaku in customary marriage and its implications for the protection of women’s rights to marital property, focusing on the Decision of the Palangka Raya High Court Number 63/PDT/2020/PT. PLK. A normative juridical approach is applied to explore the tension between customary law and national law, especially regarding the transfer of land without the legal wife's consent. The findings reveal that the transfer of jointly owned land as palaku without explicit spousal consent violates national legal principles. The decision reflects gender inequality and legal gaps that fail to adequately protect women in the national justice system. This study highlights the urgent need to harmonize customary law with national law in order to uphold substantive justice, particularly in divorce cases involving high-value assets.